Effects of Intraperitoneal Thymoquinone on Chronic Neuropathic Pain in Rats - Amin, Bahareh; Taheri, Mohammad Mehdi Heravi; Hosseinzadeh, Hossein (Planta Medica, 2014)
In this study, we evaluated the protective effects of thymoquinone, the major constituent of Nigella sativa seeds on the neuropathic pain of rats with chronic constrictive injury of the sciatic nerve. Rats received repeated administration of thymoquinone (1.25, 2.5, and 5 mg/kg, i. p.) once a day for 14 days, beginning immediately after the nerve injury. Mechanical allodynia, cold allodynia, and thermal hyperalgesia were assessed with the von Frey filament, acetone drop, or radiant heat stimulus, respectively. Recent evidence points towards a role of oxidative stress, spinal glia activation, and cell death in the pathogenesis of neuropathic pain. Ionized calcium-binding adapter molecule 1 (a marker of microglia), glial fibrillary acidic protein (a marker of astroglia), Bcl2-associated X protein (a proapoptotic protein), and B-cell lymphoma protein 2 (an antiapoptotic protein) were measured using Western blot on days 3, 7, and 14 post chronic constrictive injury. The changes in the protein levels of malondialdehyde and glutathione, biomarkers of oxidative stress, were assessed by spectrophotometric assay on day 14 post chronic constrictive injury. Repeated treatment with thymoquinone (2.5 and 5 mg/kg) significantly alleviated behavioral signs of neuropathic pain. In the lumbar spinal cord of neuropathic rats, ionized calcium-binding adapter molecule 1 and Bcl2-associated X protein increased on day 3 post chronic constrictive injury, whereas B-cell lymphoma protein 2 did not significantly change. After repeated thymoquinone administration, the elevated Bcl2-associated X protein and ionized calcium-binding adapter molecule reduced on day 3, while the level of B-cell lymphoma protein 2 was even stimulated. Ionized calcium-binding adapter molecule and Bcl2-associated X protein/B-cell lymphoma protein 2 ratio declined by days 7 and 14; consequently, there were no significant differences among groups. No or little change was observed in the glial fibrillary acidic protein content during the study. Chronic constrictive injury produced a significant increase in the levels of malondialdehyde and decrease in the contents of glutathione on day 14. Thymoquinone treatment (2.5 and 5 mg/kg) restored the levels of malondialdehyde. High dose of thymoquinone (5 mg/kg) also reversed the decreased glutathione in the injured animals. Our results indicate that, microglia, apoptotic factors, and oxidative stress rather than astroglia contribute to the pathogenesis of chronic constrictive injury, and thymoquinone plays an anti-nociceptive role possibly by antioxidant effects and inhibition of microglia activity.
Keywords: thymoquinone; Nigella sativa; Ranunculaceae; chronic constriction injury; apoptosis; oxidative stress; glia